Representation and iconographic continuity of temples from the Early Horizon to the Late Horizon and the Viceroyalty Period (700 B.C – A.D 1615) - Calero Flores, Jorge A. (2021)
This research shows the iconographic continuity of public architecture or temples, since 700 BC to 1615 A C, representation that begins in the Early Horizon with the scene present in the pluma Echenique (700 to 600 years BC), where two celebrants are seen flanking a circular temple with two ofrendatories. Subsequently, this first architectural iconography is represented in the form of the uppercase letter "H", preferably in early styles, and then it is inverted in late iconography, taking the form of the uppercase letter "I", which continues until colonial era in 1615, a situation evidenced by Guamán Poma de Ayala (1615), who records characters from the Inca period and the colonial period, the same ones who wear the icon of the inverted “H” or the “I” representative of the religious architecture.